2018
DOI: 10.3390/antiox7090122
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of the Mammalian Methionine Sulfoxide Reductase System and Related Diseases

Abstract: This review article describes and discusses the current knowledge on the general role of the methionine sulfoxide reductase (MSR) system and the particular role of MSR type A (MSRA) in mammals. A powerful tool to investigate the contribution of MSRA to molecular processes within a mammalian system/organism is the MSRA knockout. The deficiency of MSRA in this mouse model provides hints and evidence for this enzyme function in health and disease. Accordingly, the potential involvement of MSRA in the processes le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 55 publications
1
29
0
8
Order By: Relevance
“…It has been demonstrated that the oxidation of methionine impairs the reverse transport of cholesterol through apolipoprotein A-I [43]. Furthermore, a dysfunction in Met SO reductase has been linked with increased cell proliferation, degradation of extracellular matrix, interfering with key signaling processes, and cancer severity [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the oxidation of methionine impairs the reverse transport of cholesterol through apolipoprotein A-I [43]. Furthermore, a dysfunction in Met SO reductase has been linked with increased cell proliferation, degradation of extracellular matrix, interfering with key signaling processes, and cancer severity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, methionine oxidation can also impact on protein activity indirectly by coupling oxidative signals to protein phosphorylation-dephosphorylation [ 15 , 16 ]. On the other hand, there is abundant evidence that the dysregulation of this methionine oxidation-reduction cycle could be the basis of multiple diseases [ 17 ]. Not surprisingly, the interest in characterizing methionine oxidation has been revived and a number of proteome-wide studies of methionine oxidation has been reported in the past few years [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that MsrB1 is mainly expressed in the cytosol and nucleus (by contrast, MsrB2 and MsrB3 are only found in the mitochondria and/or endoplasmic reticulum) [ 6 ]. Selenium and selenoproteins like MsrB1 have been found to be important for human health [ 7 ] but their physiological and cellular roles remain to be established.…”
Section: Introductionmentioning
confidence: 99%